Allocation of Male and Female Family Labor Resources in Cattle Livestock Businesses in West Kawangkoan District, Minahasa Regency: A Simultaneous Approach - J.K. Umboh, Sintya; Erwin Wantasen; Boyke Rorimpandey (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
The labor production factor was an important production factor and needs to be taken into account in the production process. This study aims to find out how much the allocation of male and female labor in the family and analyze simultaneously the factors that influence the allocation of male and female labor resources in the family in the cattle business in West Kawangkoan District, Minahasa Regency. A survey method using interview techniques on cattle rancher household respondents, an econometric approach with a simultaneous equation model and SAS 9.4 software analyzed was used in study. The research showed male and female workers in the family in the cattle business are assessed as the supply or outpouring of male and female workers for the cattle business. In conclusion, the outpouring of male and female labor in the family was significantly influenced by labor wages, allocation of capital assistance, the number of cows reared, the number of cattle sold, and household income. Farm households will respond positively by allocating male labor in the family for the cattle business if there is an increase in the level of labor wages, capital assistance, and household income.